The creation performance of Tang Ong Song Pok - Narksen, Supat (Asian Journal of Arts and Culture, 2021)
The study of the creation of performance, costume and accessories has the objective to create the performance conveying Nora’s dressing of Nora Yai’s dressing style (Nora is called for the Classical Thai Tune of Southern of Thailand), posture, style of dance and patterns of dressing from documents, observations, interviews from the Nora’s artists as well as experiences of creators being analyzed into the knowledge based on the concept of creative theory in 7 steps of Emeritus Prof. Dr. Surapon Wirunrak and being presented in the form of creative dance art adapted from traditional dance with the creative dance moves created from 20 prototypical dance moves of Nora, 6 dance moves imitating from the nature and 23 new creative dance moves. The pattern of performance is divided into 3 parts as follows; The first part is the Mantra character. 3 male performers gradually release in the rhythm of the drum and spin one round and then dance to Pleng Patcha with the first performer writing the character “นะ” (na), “มะ” (ma). The second performer writes the character “อะ” (Ah) and the third performer writes “อุ” (au). After that they dance to summon the holy thing. The second part is the dressing grace. The performers make the dance moves with singing Thai octameter poem of Nora in the melody of drum known as Tub and in the melody of hexameter poem transmitting the importance and costume of Nora’s dressing. The third part is the delicate worship to teachers. The performers make the dance moves in the song of worship teacher with 3 dance moves representing the delicacy, stability and expertise and dance of Pleng Krai throughout Pleng Ched to get back the stage. The creation, the dressing style of the traditional Nora costume as Nora’s dressing, the singing in a southern accent and the traditional and recreated melody of southern folk music.